1980
DOI: 10.1002/bip.1980.360190509
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of protein structure as expressed in the distribution of hydrogen exchange rate constants

Abstract: SynopsisHydrogen exchange kinetics of proteins provide information about the dynamics of their structure. T h e interpretation of experiments has been limited by dilf'iculty in identifying individual rate constants. In order to invert the kinetic data, and to gain inlormation about. the individual reacting sites, we introduce a Laplace inversion technique and obtain the distribution function of rate constants hy which the intricate reaction proceeds. A series of carefully overlapped experiments were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
34
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 24 publications
8
34
1
Order By: Relevance
“…151 Similar conclusions were drawn based on isotope exchange experiments using azurin, myoglobin and lysozyme in the presence of glycerol. 149,150,[152][153][154] Carpenter and co-workers used FTIR spectroscopy to monitor the native state hydrogen exchange of three different proteins (RNase A, RNase S, and Cyt-C) in the presence and absence of sucrose. 147 In this study, sucrose was shown to increase the thermodynamic stability of all three proteins in a concentration dependent manner.…”
Section: Effects Of Ligands Osmolytes and Metal Ionsmentioning
confidence: 99%
“…151 Similar conclusions were drawn based on isotope exchange experiments using azurin, myoglobin and lysozyme in the presence of glycerol. 149,150,[152][153][154] Carpenter and co-workers used FTIR spectroscopy to monitor the native state hydrogen exchange of three different proteins (RNase A, RNase S, and Cyt-C) in the presence and absence of sucrose. 147 In this study, sucrose was shown to increase the thermodynamic stability of all three proteins in a concentration dependent manner.…”
Section: Effects Of Ligands Osmolytes and Metal Ionsmentioning
confidence: 99%
“…The analysis of hydrogen-deuterium exchange kinetics provides a means to gain further insight into the structure and dynamics of the protein, and to identify sub-molecular motional domains (22)(23)(24). The H/D exchange kinetics can be obtained by ATR-FTIR spectroscopy, applied to film samples.…”
mentioning
confidence: 99%
“…Caution must nevertheless be exercised in interpreting the results of such a procedure (16,17). In fact, it is unlikely that the distribution of lifetimes is so discontinuous, especially in experiments on unfractionated tRNA.…”
Section: Discussionmentioning
confidence: 99%